1976
DOI: 10.1126/science.948750
|View full text |Cite
|
Sign up to set email alerts
|

Binding of [14 C ] Parathion in Soil: A Reassessment of Pesticide Persistence

Abstract: A steady decrease of extractable [14C] parathion residues in soils over a 1-month incubation period was accompanied by an increase of unextractable, bound 14C-labeled residues, resulting finally in total recoveries of extracted plus bound residues of 80 to 87 percent of the applied radiocarbon. Soils containing bound residues were nontoxic to fruit flies. Binding of 14C-labeled residues was related to the activity of soil microorganisms; soil sterilization resulted in a reduction of binding by 58 to 84 percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

1979
1979
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 16 publications
4
37
1
Order By: Relevance
“…This may be related to the different nature of soils. The slow build-up of bound pesticide residues with time has been reported by Katan et al, 1976. To determine if DDT was degraded in soil, the methanol extractable 14 C-residues were qualitatively and quantitatively determined by gas liquid chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…This may be related to the different nature of soils. The slow build-up of bound pesticide residues with time has been reported by Katan et al, 1976. To determine if DDT was degraded in soil, the methanol extractable 14 C-residues were qualitatively and quantitatively determined by gas liquid chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas it has been shown that p-nitrophenol can be mineralized by P. aeruginosa after its liberation from parathion by P. stutzeri in a chemostat system (4), and the same association showed a promise for the accelerated degradation of parathion in contaminated soils (5), reductive pathways lead to the formation of aminoparathion and p-aminophenol (15,19). According to a recent report (11), the latter compound can become stabilized as soil-bound residue. Because of the position of the "4CO2 label, our experiments do not indicate whether the metabolisam in the rhizosphere favors or discourages the formation of such soilbound residues.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced mobility and biocidal activity due to bonding to humic substances are often described (5)(6)(7)(8). It is in some cases supported by various experimental results, that parent molecules or metabolites are bound to the humic matrix either by covalent bonding (9)(10)(11)(12)(13)(14)(15)(16)51), ionic bonding (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), charge transfer complexes (29)(30)(31)(32)(33), ligand exchange (34,35), hydrogen bonding (23,31,(36)(37)(38)(39)(40), van der Waals forces (22,(41)(42)(43)(44), hydrophobic sorption (45)(46)(47)(48)(49)…”
Section: Comission On Pesticide Chemistrymentioning
confidence: 90%
“…As recently discussed (82), innovatively applied analytical methods like silylation of soil organic matter constituents, solid-phase microextraction, thermodesorption, pyrolysis-GC-MS and sophisticated bioassays will broaden the insight into the field of bound residue research. The combination of analytical approaches with the use of stable and radioactive isotope labelling techniques ( 12 C, 13 C, 14 C, 15 N, 31 P) can be extremely advantageous in this respect. In addition, aspects of soil biology in relationship to soil organic matter turnover can be addressed and may contribute to enlarge the knowledge in this field, respectively.…”
Section: Conclusion and Research Optionsmentioning
confidence: 99%